Purification and biochemical characterization of a mycelial alkaline phosphatase without DNAase activity produced by Aspergillus caespitosus - Guimarães, L H S; Júnior, A B; Jorge, J A; Terenzi, H F; Polizeli, M L T M (Folia microbiologica, 2007)
Biochemical properties of a termostable alkaline phosphatase obtained from the mycelium extract of A. caespitosus were described. The enzyme was purified 42-fold with 32% recovery by DEAE-cellulose and concanavalin A-Sepharose chromatography. The molar mass estimated by Sephacryl S-200 or by 7% SDS-PAGE was 138 kDa and 71 kDa, respectively, indicating a homodimer. Temperature and pH optima were 80 degrees C and pH 9.0. This enzyme was highly glycosylated (approximately 74% saccharide content). The activity was enhanced by Mg2+ (19-139%), NH4+ (64%), Na+ (51%) and Mn2+ (38%). 4-Nitrophenyl phosphate (4-NPP) was preferentially hydrolyzed, but glucose 1-phosphate (93%), UTP (67%) and O-phosphoamino acids also acted as substrates. V(lim) and K(m) were 3.78 nkat per mg protein and 270 micromol/L in the absence of Mg2+ and 7.35 nkat per mg protein and 410 micromol/L in the presence of Mg2+, using 4-NPP as substrate. The purified alkaline phosphatase removed the 5'-phosphate group of a linearized plasmid without showing DNAase activity, indicating its potential for recombinant DNA technology.